A agrobiodiversidade nas terras indígenas guarani Nhandewa no norte do Paraná: memória, resgate e perspectivas - Almeida, Thiago Valente Vieira de (2012)
The importance of the farmers themselves hold their traditional varieties of seeds becomes even more relevant to indigenous peoples, both for the richness of ethnic knowledge developed, and the rescue of these practices in the current context of degradation and erosion of diversity, imposed by the dominant monocultural model. This study characterized the situation of indigenous agrobiodiversity in the north of Paraná state, indigenous territory Terra Indígena Laranjinha and Terra Indígena Pinhalzinho , inhabited by Nhandewa Guarani Indians. Through an ethnographic study examined the memory of the Guarani Indians of their various tradicional seeds, their distinct characteristics and uses, as well as agricultural practices were employed by ancians. The wishes of indigenous agrobiodiversity rescue and the difficulties facing the dominant model of production in the field were also registered. Terra Indígena Pinhalzinho performed the first Feira de Troca de Sementes Crioulas/Tradicionais and directed efforts to locate and produce the varieties of rice, beans, potatoes, cassava and maize indigenous. Respondents shall ensure that the presence of these seeds help to rescue cultural universe, strengthening spiritual Guarani lifestyle.